Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.2174/138161282104141204141851
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotherapy of Dilated Cardiomyopathy

Abstract: The pharmacological treatment of dilated cardiomyopathy overlaps with the treatment of heart failure. The primary objective of this treatment is to slow the progression of disease and improve quality and length of life. All patients, including those with asymptomatic dysfunction of the left ventricle, ought to receive angiotensin converting enzyme inhibitors, (in the case of intolerance, angiotensin receptor blockers), and beta blockers. The results of studies involving aliskiren have been, so far, disappointi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Together with the result of this experiment on losartan, we conclude that ARBs can improve the electrophysiological changes induced by atrial stretch, the mechanism of which involves the blocking of the AT 1 receptor and be beneficial to preventing the electrophysiological remodeling during AF. Previous studies of the relationship between ARBs and AF were mainly focused on the effect of ARBs on the remodeling of atrial tissues and structures (2,4,6). The present study showed that atrial electrophysiological remodeling also occurs under the action of the medicines.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Together with the result of this experiment on losartan, we conclude that ARBs can improve the electrophysiological changes induced by atrial stretch, the mechanism of which involves the blocking of the AT 1 receptor and be beneficial to preventing the electrophysiological remodeling during AF. Previous studies of the relationship between ARBs and AF were mainly focused on the effect of ARBs on the remodeling of atrial tissues and structures (2,4,6). The present study showed that atrial electrophysiological remodeling also occurs under the action of the medicines.…”
Section: Discussionsupporting
confidence: 57%
“…Renin-angiotensin system (RAS) is an important humoral regulation system composed of renin, angiotensin, and its receptor that plays a fundamental role in maintaining the cardiovascular normal development, functional homeostasis, balance of electrolyte and body fluid, as well as regulation of blood pressure. Previous reports have shown that experimental atrial arrhythmias were closely involved in RAS abnormalities (1)(2)(3)(4). Clinical investigations also found that RAS blockers, including angiotensin-converting enzyme inhibitors and angiotensin II type 1 receptor (AT 1 R) blockers (ARBs), were effective in the treatment of atrial fibrillation (AF) (5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…In chronic heart failure application of these drugs, in combination with the conventional β-blocker + ACE inhibitor + diuretic therapy, gives a chance to the "pharmacologically suppressed" heart to enhance its mechanical performance, which may significantly improve the quality of life of the patients. Since omecamtiv mecarbil can be considered as a representative of a novel group of Ca 2+ sensitizers, the question whether conventional Ca 2+ sensitizers or myosin activators will provide better therapeutic results has to be answered with no doubt (Spinarova and Spinar 2015). Further clinical and preclinical studies are required to reveal and to discriminate between their potential effects on cardiac oxygen consumption and cardiac rhythm during various cardiac pathologies (Givertz et al 2013;Hasenfuss and Teerlink 2011;Kehat 2012;Rajapreyar et al 2014;Selby and Teerlink 2013;Tarone et al 2014).…”
Section: Perspectivesmentioning
confidence: 99%
“…Many former treatments have been applied to cure CMP, including medical therapy, cardiac pacemaker implantation, and heart transplantation. However, these traditional therapies cannot fundamentally solve the problems of cardiomyocyte regeneration and cardiac function reconstruction, making the therapeutic effect of cardiomyopathy unsatisfactory [1, 2]. In recent studies, with the newly emerged stem cell therapy, myocardial regeneration and cardiac function reconstruction have become possible [3, 4].…”
Section: Introductionmentioning
confidence: 99%